2021
DOI: 10.3390/f12070813
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Equity and Regional Management of Some Urban Green Space Ecosystem Services: A Case Study of Main Urban Area of Xi’an City

Abstract: Urban green spaces can provide many types of ecosystem services for residents. An imbalance in the pattern of green spaces leads to an inequality of the benefits of such spaces. Given the current situation of environmental problems and the basic geographical conditions of Xi’an City, this study evaluated and mapped four kinds of ecosystem services from the perspective of equity: biodiversity, carbon sequestration, air purification, and climate regulation. Regionalization with dynamically constrained agglomerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…During the study period, rapid urban spatial expansion encroached on a large amount of ecological land in the central plains of XMA, including cropland, as well as forest and grassland, exacerbating the degradation of ESs (Puplampu & Boafo, 2021;Tao et al, 2020), especially in Xi'an (Figure 3A,B). The high degree of urbanization and drastic expansion of man-made landscapes has led to a shortage of ES supply in most of Xi'an, except for the northern part of the Qinling Mountains (Figure A1), which is consistent with previous studies (Dang et al, 2021;Liu et al, 2021). Meanwhile, areas of cropland, forest land, and grassland were affected by the increasing demand of the growing population, the project of returning cropland to forest and grassland, and the ecological fallow policy of Western development strategy.…”
Section: Past-future Spatial Pattern Of the Es Supply Risksupporting
confidence: 90%
“…During the study period, rapid urban spatial expansion encroached on a large amount of ecological land in the central plains of XMA, including cropland, as well as forest and grassland, exacerbating the degradation of ESs (Puplampu & Boafo, 2021;Tao et al, 2020), especially in Xi'an (Figure 3A,B). The high degree of urbanization and drastic expansion of man-made landscapes has led to a shortage of ES supply in most of Xi'an, except for the northern part of the Qinling Mountains (Figure A1), which is consistent with previous studies (Dang et al, 2021;Liu et al, 2021). Meanwhile, areas of cropland, forest land, and grassland were affected by the increasing demand of the growing population, the project of returning cropland to forest and grassland, and the ecological fallow policy of Western development strategy.…”
Section: Past-future Spatial Pattern Of the Es Supply Risksupporting
confidence: 90%
“…In formula (2), k is the number of training samples: X is N-dimensional space, X ∈ RN; y is a class label, and y ∈ f− 1,+1g. If there is a vector W perpendicular to the linear hyperplane (determining the direction of the discrimination plane) and a scalar b showing the offset of the discrimination hyperplane from the origin, these classes are considered to be linearly separable.…”
Section: Xi'an Green Space Information Extraction Methodmentioning
confidence: 99%
“…It has important ecological auxiliary function for urban development and progress. It is an important indicator of urban ecological civilization construction and plays an important role in regulating urban ecological environment [2].…”
Section: Introductionmentioning
confidence: 99%
“…Dang, H. et al discussed the influence of urban green space on urban ecosystems in the process of urbanization, and the imbalance in the distribution of green ecological space will make the residents unable to get a more livable ecological environment. After analyzing the environmental status and geographic conditions of Xi'an City, it was shown that urbanization needs to reduce the destruction of urban green space communities and improve biodiversity [20]. Pamucar, D. et al analyzed the reciprocity between urban planning and urban context in the process of urbanization, using 17 United Nations member states as examples.…”
Section: Review Of Research On New Urbanization and Integrated Urban-...mentioning
confidence: 99%